Developing Malay traditional dance model for preschoolers: Evidence from contextual and content needs - Zain, Azizah; Tajuddin, Siti Nor Amalina Ahmad; Ismail, Irwan Mahazir; Masnan, Abdul Halim; Saerani, Muhammad Fazli Taib Saerani; Alim, Maisarah Mohd (Jurnal Cakrawala Pendidikan, 2024)
The uniqueness of the Malay dance community should be introduced to children, so that the beauty of the dance movements will be preserved. Therefore, this study examined preschoolers' content and the contextual needs of developing the traditional Malay dance model. Quantitative studies using this survey method aim to obtain information about the context and content of traditional Malay dance models. The utilized tool was a validated questionnaire that had undergone expert validation and piloting. 125 Malaysian Ministry of Education (MOE) preschool teachers were selected as the study sample based on their experience and qualifications in Early Childhood Education. The data collected were analyzed with descriptive statistics using SPSS version 26. The findings indicate that the necessities of the context should inhibit the aspects of creative movement. The results refer to the content aspect of the model of the basic movement elements in the traditional dances of the Malay community that should be taught to the children.